Effect of rock phosphate, single super phosphate and their mixtures with FYM on yield, quality and nutrient uptake by turmeric (Curcuma longa L.) in acid alfisol of Meghalaya - Kumar, M S Venkatesh, B Majumdar, Kailash (Journal of Spices and Aromatic Crops, 2003)
A field experiment was conducted for two years on a P deficient Typ'ic Hapll/dllljof Meghalaya to study the effectiveness of rock phospha te (RP), Single Super Phosphate (SSP) and their mixtures along with FYM on turmeric. Application of P as RP or SSP alone or their Inixtures with FYM significantly increased the rhizome yield over control. There was a 50 per cent increase in rhizome yield due to FYM application. Maximum Nand P uptake, curcumin content and Phosphorus use efficiency (PUE) were recorded in RP+SSP (1:3) + FYM treatment. Post harvest analysis of soil samples indicated that soil pH was marginally reduced with FYM application while organic carbon, ECEC and available P contents increased.